2011
DOI: 10.1063/1.3568010
|View full text |Cite
|
Sign up to set email alerts
|

Fully analytic energy gradient in the fragment molecular orbital method

Abstract: The Z-vector equations are derived and implemented for solving the response term due to the external electrostatic potentials, and the corresponding contribution is added to the energy gradients in the framework of the fragment molecular orbital (FMO) method. To practically solve the equations for large molecules like proteins, the equations are decoupled by taking advantage of the local nature of fragments in the FMO method and establishing the self-consistent Z-vector method. The resulting gradients are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(15 citation statements)
references
References 99 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…A comparison of the accuracy of two and three-body expansions of DFT for the energy and gradient is found elsewhere, 65 and the cost scaling of FMO with system size has already been discussed in general. 48 The FMO analytic energy gradient has been developed for closed and open-shell Hartree-Fock (HF) [66][67][68][69][70][71] and DFT. 72 The analytic second derivative, which can be used to evaluate Raman activities, 73 has been developed only for HF 46,74 at the two-body level (FMO2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the accuracy of two and three-body expansions of DFT for the energy and gradient is found elsewhere, 65 and the cost scaling of FMO with system size has already been discussed in general. 48 The FMO analytic energy gradient has been developed for closed and open-shell Hartree-Fock (HF) [66][67][68][69][70][71] and DFT. 72 The analytic second derivative, which can be used to evaluate Raman activities, 73 has been developed only for HF 46,74 at the two-body level (FMO2).…”
Section: Introductionmentioning
confidence: 99%
“…(7)- (14) into Eq. (6) 46,67 is that the sum of all orbital response terms cancels out in FMO2 gradients and Hessians if the ESP point charge (PC) approximation, ESP-PC, is applied to all ESPs, or if the ESP-PC approximation is not used at all; 80,81 otherwise, the orbital response terms need to be evaluated. 82 Now, it is shown that the orbital response terms U ab, X,Y also cancel out for FMO3, for the same two conditions.…”
mentioning
confidence: 99%
“…We used the first structure available in each of the downloaded structures. For comparison, we performed two-body Fragment Molecular Orbital (FMO) (Fedorov & Kitaura, 2007) geometry optimizations using RHF/6-31G(d) (Francl et al, 1982; Gordon et al, 1982; Hariharan & Pople, 1973; Nagata et al, 2011) and the D3 dispersion correction (Grimme et al, 2010; Peverati & Baldridge, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it is expected that the use of the variational X-Pol energy as the monomer energy reference state in many-body energy expansion should lead to smaller corrections than other alternatives. 14 Although it is possible to obtain analytic gradients for the nonvariational, charge-embedding approaches, 35 it generally involves solution of coupled-perturbed self-consistent field equations. Sometimes the response terms in fragment-based methods have been neglected.…”
Section: Theoretical Backgroundmentioning
confidence: 99%